Freshwater Shrimp (Decapoda) in Aceh: A Promising Resource for Aquaculture Development - Putra, Dedi Fazriansyah; Abbas, Muhammadar Abdullah; Siregar, Tongku Nizwan; Wowor, Daisy (Heca Sentra Analitika, 2025)
Freshwater shrimp of the genus Macrobrachium represent an underutilized resource in Aceh Province, Indonesia, despite the region’s rich freshwater ecosystems and the global economic value of shrimp aquaculture. This study presents the first integrative assessment of the aquaculture potential of 13 Macrobrachium species collected from 27 freshwater sites across Aceh. Species were evaluated using morphological identification, ecological field surveys, literature reviews, and key biological parameters, including egg size, larval development, salinity tolerance, and local consumption. Most species exhibited r-strategist reproductive traits and prolonged larval stages, requiring brackish or marine environments, which limited their suitability for closed freshwater systems. However, M. lanchesteri displayed abbreviated larval development and completed its life cycle in freshwater, making it a strong candidate for sustainable aquaculture. M. idae was assessed as moderately suitable due to extensive supporting literature and local use. These findings highlight both the constraints and opportunities for freshwater shrimp cultivation in Aceh, providing a foundation for future research and development in aquaculture diversification and local food security.